2011
DOI: 10.1186/2045-824x-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Dermal fibroblasts display similar phenotypic and differentiation capacity to fat-derived mesenchymal stem cells, but differ in anti-inflammatory and angiogenic potential

Abstract: BackgroundMesenchymal stem cells (MSCs) are multipotent stem cells able to differentiate into different cell lineages. However, MSCs represent a subpopulation of a more complex cell composition of stroma cells contained in mesenchymal tissue. Due to a lack of specific markers, it is difficult to distinguish MSCs from other more mature stromal cells such as fibroblasts, which, conversely, are abundant in mesenchymal tissue. In order to find more distinguishing features between MSCs and fibroblasts, we studied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
109
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 43 publications
13
109
3
1
Order By: Relevance
“…Therefore, it is generally believed that the major benefits derived from transplanted stem cells are the paracrine effects of secreted molecules [17]. This hypothesis was confirmed by numerous studies showing that the CM, collected from a variety of stem cell populations, had beneficial effects on cells and tissues in vitro and in vivo [3,24]. These studies showed that various stem/ progenitor cell populations, such as MSCs or EPCs, released proangiogenic and antiapoptotic cytokines in culture, which may contribute to enhanced angiogenesis and endogenous repair [25].…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, it is generally believed that the major benefits derived from transplanted stem cells are the paracrine effects of secreted molecules [17]. This hypothesis was confirmed by numerous studies showing that the CM, collected from a variety of stem cell populations, had beneficial effects on cells and tissues in vitro and in vivo [3,24]. These studies showed that various stem/ progenitor cell populations, such as MSCs or EPCs, released proangiogenic and antiapoptotic cytokines in culture, which may contribute to enhanced angiogenesis and endogenous repair [25].…”
Section: Discussionsupporting
confidence: 48%
“…In a recent publication, the authors identifi ed the diffi culty of distinguishing between adiposederived MSCs (AD-MSCs) and human adult dermal fibroblasts in vitro -regarding their morphological appearance, phenotypic profile and differentiation potential. Both AD-MSCs and HDFas displayed similar capacity to differentiate into osteogenic, adipogenic and cardiomyogenic cell lineages (Blasi et al, 2011). Similarly, dermal-derived fi broblasts from rodent and human were shown to differentiate along the adipogenic and osteogenic lineages (Lorenz et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…32,33 We demonstrate that bMSCs consistently and efficiently chemoattract human endothelial cells in vitro, suggesting their potential involvement in promoting tumor angiogenesis. We also Figure 6.…”
Section: Discussionmentioning
confidence: 99%